(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The study’s aim is to empirically investigate the relationship between electronic service delivery and consumers attitude of money deposit banks in Yenagoa, Bayelsa State. Customers’ attitude of Yenagoa money deposit banks and the delivery of electronic services are the subjects of this study. The study used a cross-sectional research design. This study’s population consisted of three hundred and twenty (320) accessible customers of sixteen (16) registered deposit money banks in Yenagoa, Bayelsa State. Using the Taro Yamane sample size determination formula, 178-person sample was chosen. Only 168 of the questionnaires were found to be valid and useful for analysis using the Spearman Rank Correlation Coefficient and SPSS version 23 to test four (4) hypotheses. Customers’ attitude of money deposit banks in Yenagoa are positively correlated with the provision of electronic services, according to the findings. One of the suggestions was that banks should try to be more creative and innovative in how they meet the needs of customers. This could be done by improving the quality of service they provide and using marketing strategies that can increase demand for and customer satisfaction with electronic banking services.